ANALISIS SISTEM KOMPENSASI BERDASARKAN SALARY MAPPING DENGAN METODE ADHERED DAN OVERLAPPING PADA UKM XYZ - Annisa Afni Azzahra; Ditha Giri Nuranjani; Terli Edisti; Aulilah Anggraeni; Pocut Nazla Arina (PT Naureen Digital Education, 2023)
Small and Medium Enterprises (SMEs) as a sector that plays an important role in the Indonesian economy must have effective management in improving the performance of their employees, one of which is by implementing an appropriate compensation system according to the 3P principle (Pay for Position, Person, and Performance). Compensation aims to assist SMEs in achieving strategic success by taking into account internal and external fairness. This study aims to analyze the compensation system implemented by UKM XYZ. UKM XYZ is a business engaged in the culinary field operating on Jl. Raya Bubulak, RT.02/RW.12, Cilendek Bar., Kec. Bogor Bar., Bogor City, West Java and has a total of 30 employees. The compensation system applied to UKM XYZ will then be analyzed and evaluated based on salary mapping using adhered and overlapping methods. After conducting an evaluation, an ideal compensation system was found for UKM XYZ, where there was no increase in salary either using the adhered method or the overlapping method.